Chemical Mechanical Polishing Slurry for Amorphous Ge2Sb2Te5. (2015) - Song, Zhitang; Liu, Weili; Wang, Liangyong
Abstract: As flash technologies face scaling issues at 32 nm and beyond, phase change memory (PCM) emerges as the best performing candidate for scaled non-volatile memories of next generation. To fabricate PCM device with high volume and low power consumption, the structure of PCM has evolved from planar structure to confined cells, which pose challenges for chemical mechanical polishing (CMP) of the phase change material Ge2 Sb2 Te5 (GST).In this study, we discuss the properties, polishing mechanisms and slurry formulations for amorphous GST. Static etching characteristics and zeta potentials of GST powders are first explored to evaluate the chemical properties of GST. Then the polishing mechanisms of GST at pH 2 and pH 11 are discussed by means of static etching experiments, polishing performance, GST film hardness measurement, GST solubility and open circuit potential test. Finally, our efforts for GST slurry development are described. By a combination effect of inhibitors, in which one can form adsorption layer on GST by carbonyl O and the other one can further protect GST surface by forming hydrogen bond through multiple OH groups, we have overcome the corrosion issue of GST. Meanwhile, by the adsorption of the inhibitor layers on GST surface and extremely low removal rate of oxide film (<0.05 nm/min), we have achieved a self-stop GST CMP process with over-polish dishing <8 nm and oxide loss <6 nm for 60 nm GST vias. We have also resolved the issue of particle residue by using our self-formulated post-cleaning solution.